2015
DOI: 10.1016/j.idairyj.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A review of the microbiological hazards of dairy products made from raw milk

Abstract: a b s t r a c tThis review concentrates on information concerning microbiological hazards possibly present in raw milk dairy products, in particular cheese, butter, cream and buttermilk. The main microbiological hazards of raw milk cheeses (especially soft and fresh cheeses) are linked to Listeria monocytogenes, verocytotoxin-producing Escherichia coli (VTEC), Staphylococcus aureus, Salmonella and Campylobacter. L. monocytogenes, VTEC and S. aureus have been identified as microbiological hazards in raw milk bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(99 citation statements)
references
References 101 publications
1
89
0
9
Order By: Relevance
“…It is important to note that even dairy products made from raw milk can cause severe health effects due to the unwanted microorganisms [6]. In addition to Listeria, a wide variety of other organisms occasionally found in raw milk make people sick.…”
Section: Example Of Raw Beverage Hazards-raw Milkmentioning
confidence: 99%
“…It is important to note that even dairy products made from raw milk can cause severe health effects due to the unwanted microorganisms [6]. In addition to Listeria, a wide variety of other organisms occasionally found in raw milk make people sick.…”
Section: Example Of Raw Beverage Hazards-raw Milkmentioning
confidence: 99%
“…In their study, Bianchi et al (2013) concluded that unpasteurized milk can be a vehicle for a variety of microorganisms (Listeria spp., Salmonella, and Campylobacter) and that outbreaks related to cheeses made with unpasteurized milk are also common (Gould et al, 2014). The development of a disease after consumption of contaminated dairy products made from raw milk depends on several factors, such as the pathogenicity of the bacteria strain, the number of ingested microorganisms, the physiological state of the microorganism, and the health condition of the consumer at the moment of ingestion (Verraes et al, 2015).…”
Section: Foodborne Disease Outbreaks Related To Dairy Productsmentioning
confidence: 99%
“…Staphylococcus aureus, Salmonella spp., Listeria monocytogenes and Escherichia coli O157:H7 are the most frequent potential pathogens associated with milk or dairy products in industrialized countries (Jakobsen et al, 2011) and are therefore the main microbiological hazards linked to raw milk (Kousta et al, 2010;Yang et al, 2012;Claeys et al, 2013) and raw cheese (Verraes et al, 2015). Raw milk provides a potential growth medium for the development of bacteria that can be controlled or destroyed through the pasteurization process (Arqués et al, 2015).…”
Section: Bacteria Involved In Dairy Product Contaminationmentioning
confidence: 99%
See 2 more Smart Citations